Welding codes, standards, and specifications - Mouser, Jeffrey D. (McGraw-Hill, 1998)
Meant as a reference for engineers, welders, and inspectors, this book deals with structural steel and welding codes for buildings. It brings together the American Welding Society Codes, Uniform Building Codes, Standard Building Codes, American Institute of Steel Construction Codes, and BOCA National Building Codes.